The Impact of Digital Integrated Reporting on the Influence of Financial Performance on Firm Value - Ningdiyah, Endra Wahyu; Asyik, Nur Fadjrih; Fidiana, Fidiana (Journal of Accounting Science, 2024)
General Background: The increasing complexity of global financial markets necessitates enhanced transparency and comprehensive reporting, leading to the adoption of digital integrated reporting (DIR) as a framework to provide stakeholders with concise, strategic insights into company performance. Specific Background: In Indonesia, the integration of DIR into financial reporting practices has become crucial, particularly for firms within the LQ-45 index on the Indonesia Stock Exchange, which are considered leaders in corporate governance and reporting standards. Knowledge Gap: Despite DIR's recognized importance, its moderating role in enhancing the relationship between financial performance metrics—Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER)—and firm value remains underexplored. Aims: This study aims to evaluate the effect of ROA, CR, and DER on firm value, considering DIR as a moderating factor, within Indonesian LQ-45 companies during 2019–2021. Results: The findings reveal that ROA and DER significantly impact firm value, while DIR positively moderates the effects of ROA and DER on firm value. Novelty: This research uniquely identifies DIR's moderating influence, offering a fresh perspective on how digital reporting mechanisms can enhance the predictive power of traditional financial metrics. Implications: The study underscores the strategic importance of DIR in corporate reporting, suggesting that enhanced disclosure can lead to increased investor confidence and potentially higher firm valuation, thereby informing policy and practice in corporate governance and financial reporting​.